Peculiarities in household solid waste management in Nigeria: a quick review - Fakunle, Sunday Olutayo (Frontiers in Sustainability, 2024)
Evidence abounds to indicate the prevalence of indiscriminate disposal of household solid waste as a practice in Nigeria. This practice contributes to green crime and jeopardises public health. Therefore, the focal point of several academic papers has been household solid waste management. The objective of the current study was to make a rapid review on practices that scholars have recommended for household members to take proper care of their waste made of paper, cellophane, plastic, metal and wooden material and the peculiarities of these recommended practices in Nigeria with implications for waste management practices in developing countries worldwide. The study adopted the systematic review method to explore findings in the available relevant studies that were published within the years 2017 and 2023 to depict the current situations of the study's subject matter in Nigeria. The current study sorted out these findings into themes. The review pinpointed several recommended practices such as zerowaste policy, waste minimization/reduction, and various disposal methods to manage the household solid waste and the major factors responsible for the setbacks these practices have faced. The review further highlighted gaps in existing studies which could form the basis for prospective studies on household solid waste management.